Dopłaty do kapitału źródłem finansowania działalności rozwojowej w spółkach hodowlanych ANR - Lewandowska, Izabela (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
This article describes subsidies for capital as a source of founding development activities in breeding companies. Farm crop and livestock companies, that have particular importance to the national economy, which rights of shares or stocks are performed by the Agricultural Property Agency, received financial support of 293,2 milion PLN in years 2001–2007. The subsidies for capital have been allocated to finance investment, acquisition of biological and breeding material, research and implementation projects and cover balance losses. The investment program taken in companies led to the upgrading of the material – technical base of breeding and created opportunities for strategic farms to become companies guaranteeing high efficiency in farming and production on elevated economic and financial level48